THE CORRELATION BETWEEN SIMPLE PRESENT TENSE MASTERY AND DESCRIPTIVE PARAGRAPH WRITING ABILITY OF THE ELEVENTH-GRADE STUDENTS OF SMAN 1 BLAHBATUH - Ni Wayan Rima Haryati (PRODI PENDIDIKAN BAHASA INGGRIS INSTITUT PENDIDIKAN DAN BAHASA INVADA, 2023)
The present study used an ex-post facto research design that figure out the correlation between simple present tense mastery and descriptive paragraph writing ability of the eleventh-grade students of SMAN 1 Blahbatuh in academic year 2022/202. The present research sample consisted of 60 students from 247 populations of the eleventh-grade students of SMAN 1 Blahbatuh in academic year 2022/2023. Chosen by random sampling method that chosen by the teacher. The data were collected by administering the research instrument in the form of sentence writing test and descriptive paragraph tests. The obtained data were analyzed by using Pearson product-moment correlation and T-test. The data analysis result showed that the students’ simple present tense mastery correlated with their descriptive paragraph writing ability. To sum up, the present research findings finally confirmed that there was a significant correlation between simple present tense mastery and descriptive paragraph writing ability of the eleventh-grade students of SMAN 1 Blahbatuh in academic year 2022/2023.